2009
DOI: 10.4269/ajtmh.2009.09-0160
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus Brain Abscesses Associated with Hepatic Amebiasis in a Non-neutropenic Man in Senegal

Abstract: Abstract. A non-neutropenic man living in Senegal was repatriated to France for liver amebic abscesses associated with brain abscesses presumed to be of amebic origin. Surprisingly, the post-mortem examinations of brain abscesses showed Aspergillus flavus . The route of infection by A. flavus in this particular context is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…While specific pulmonary imaging findings can be suggestive of IA, it has recently been noted that radiologic findings of invasive mold infections among solid organ transplant recipients are more varied than previously thought and CNS IA has no consistent radiographic appearance. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Additionally, serum galactomannan, which was negative in our patient, is only 55.6% sensitive and 93.9% specific for IA in liver transplant patients. 28 While our patient was an organ recipient, he had no typical clinical or chest imaging findings of IA, no specific brain imaging findings of IA and a negative serum galactomannan.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While specific pulmonary imaging findings can be suggestive of IA, it has recently been noted that radiologic findings of invasive mold infections among solid organ transplant recipients are more varied than previously thought and CNS IA has no consistent radiographic appearance. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Additionally, serum galactomannan, which was negative in our patient, is only 55.6% sensitive and 93.9% specific for IA in liver transplant patients. 28 While our patient was an organ recipient, he had no typical clinical or chest imaging findings of IA, no specific brain imaging findings of IA and a negative serum galactomannan.…”
Section: Discussionmentioning
confidence: 90%
“…Upon performing a PubMed-based literature review dating from 2005 to present, we identified19 previously reported cases of CNS IA in patients with liver disease of any kind (Table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Most patients were male with a median age of 38 (range 12 to 68). Four of the 19 patients never received a transplant, and had severe liver with CSF PCR, while in two cases, diagnosis was inferred from cultures from other sites.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
“…Environment plays an important role in the epidemiology of A. flavus human infection. Infections due to this species are more prevalent in dry and hot climatic regions, and some clinical cases reported in France are imported infections contracted in Africa [24,25,32]. Infections are mostly acquired by exposure to A. flavus spores in the environment, and nosocomial infections in hospitals have also been reported from surgery unit air and surface [30,92].…”
Section: Discussionmentioning
confidence: 99%
“…A. flavus is also the first agent of skull base aspergillosis, whose typical form is malignant external otitis [12][13][14][15][16][17], and the principal risk factor is diabetes [18]. A. flavus could also be implicated in many other clinical forms such as pulmonary invasive aspergillosis [19][20][21][22], chronic rhinosinusitis [23], brain abscesses [24], myositis [25,26], arthritis [27], spondylodiscitis [28,29], endocarditis [30,31], mediastinitis [32], eumycetoma [33], and allergic [34] or hypersensitivity syndromes like hot tub pneumonitis [35].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroaspergillosis is an uncommon infection associated with an exceedingly high mortality. The diagnosis of neuroaspergillosis is difficult, often made at the terminal stage of disease or on autopsy [1]. Perhaps due to the greater penetration into the central nervous system (CNS), voriconazole treatment greatly improved clinical outcomes with a survival rate of 30% in high-risk patients [2,3].…”
mentioning
confidence: 99%